Efficiency of Polymeric Membrane Graphene Oxide-TiO2 for Removal of Azo Dye - Elahe Dadvar; Roshanak Rezaei Kalantary; Homayon Ahmad Panahi; Majid Peyravi (Journal of Chemistry)
Achieving the desired standard of drinking water quality has been one of the concerns across water treatment plants in the developing countries. Processes such as grid chamber, coagulation, sedimentation, clarification, filtration, and disinfection are typically used in water purification plants. Among these methods, unit filtration which employs polymers is one of the new technologies. There have been many studies about the use of semiconductive TiO2 with graphene oxide (GO) on the base of different polymeric membranes for the removal of azo dyes, especially methylene blue (MB). Polymeric GO-TiO2 membranes have high photocatalytic, antifouling property and permeate the flux removal of organic pollutants. The aim of this study was to investigate the characteristics of different polymeric membranes such as anionic perfluorinated polymer (Nafion), cellulose acetate, polycarbonate (PC), polysulfone fluoride (PSF), and polyvinylidene fluoride (PVDF). The result of this study showed that the GO-TiO2 membrane can be used in the field of water treatment and will be used for the removal of polycyclic aromatic hydrocarbons (PAHs) from wastewater.